Islamic Populism in The Public Sphere and Interest in 212 Action - Nurus Shalihin; M Yusuf (Indonesian Journal of Religion and Society, 2022)
This research aimed to examine the importance of Islamic populism against the “212 Action” in Indonesia using qualitative methods. The primary data were collected through in-depth interviews with several informants and analyzed using the analysis offered by Miles and Huberman. The results showed three interests of Islamic populism towards the 212 Action. First, it had been used as a space for a parade of forces to rally the masses and unite militant religious organizations. Second, it made a space to break down the stereotypes against this group. Third, it had been used to instill unity ideology and strengthen the people’s strength. In conclusion, Islamic populism had made the 212 Action a space to convey some of its private interest agenda to the public sphere.